Variation at 3p24.1 and 6q23.3 influences the risk of Hodgkin’s lymphoma - Frampton, Matthew; Silva Filho, Miguel Inacio da; Broderick, Peter; Thomsen, Hauke; Försti, Asta; Vijayakrishnan, Jayaram; Cooke, Rosie; Enciso-Mora, Victor; Hoffmann, Per; Nöthen, Markus Maria; Lloyd, Amy; Holroyd, Amy; et al. (Nature Communications, 2013)
In addition to HLA, recent genome-wide association studies (GWASs) of Hodgkin’s lymphoma (HL) have identified susceptibility loci for HL at 2p16.1, 8q24.21 and 10p14. In this study, we perform a GWAS meta-analysis with published GWAS (totalling 1,465 cases and 6,417 controls of European background), and follow-up the most significant association signals in 2,024 cases and 1,853 controls. A combined analysis identifies new HL susceptibility loci mapping to 3p24.1 (rs3806624; P=1.14 × 10−12, odds ratio (OR)=1.26) and 6q23.3 (rs7745098; P=3.42 × 10−9, OR=1.21). rs3806624 localizes 5′ to the EOMES (eomesodermin) gene within a p53 response element affecting p53 binding. rs7745098 maps intergenic to HBS1L and MYB, a region previously associated with haematopoiesis. These findings provide further insight into the genetic and biological basis of inherited susceptibility to HL.